Tinjauan Yuridis Gugatan Wanprestasi Terhadap BUMN Atas Sengketa Perjanjian Sewa Beli Tanah Dan Bangunan ( Studi Putusan No. 276/PDT.G/2020/PN Mdn ) - Rinaldi Ginting; Aulia Rosa Nasution; Mahalia Nola Pohan (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
Default is a condition where the debtor does not carry out his obligations that have been specified in the agreement. In addition to not carrying out its obligations as specified in the agreement, default can also occur where the debtor does not carryout his obligations asstipulated in the law. Research method used is normative yuridicial research, the nature of the research used is descriptive, data collection technique is with do library research and interviews. The results of the study default lawsuit against state owned enterprise on land and buildings sale agreement disputes because where Sumurung Siregar wanted to buy the official house he once occupied but when the installment of the house wascompleted the Director of PT.PLN did not reverse the deed of the official house to the name of Samurung Siregar. So that in this sale and purchase agreement the judge judges by listening to witness statements and examining the existing evidence. From research conducted it can be concluded that the cause of default is that in resolving the default dispute, deliberation must first be carried out so as not to harm the parties if they do not get a solution then go to court.